Enhancing flood resilience through collaborative modelling and multi-criteria decision analysis. (MCDA) - Evers, Mariele; Almoradie, Adrian; Madruga de Brito, Mariana (Springer, 2018)
Die Arbeit beschreibt und bewertet den Einsatz der Methode der sogenannten multikriteriellen Entscheidungsunterstützung (Multi-Criteria Decision Analysis (MCDA)) im Bereich der Hochwassergefährdung bzw. Hochwasservorsorge von Städten.

The concept of urban resilience has emerged in the context of flood risk management (FRM) from the need to consider the capability of the society to cope with floods. Whilst there has been much discussion about flood resilience, challenges still remain on how to enhance it. Participation of key stakeholders in the decision-making process has the potential to enrich the resilience of communities as they become more informed, learn from each other and trust is built amongst them. Despite the advantages of participation, community members and decision-makers do not play an active role in flood resilience studies. Therefore, inter- and transdisciplinary approaches may help to overcome these limitations whilst promoting social learning towards resilience building. This chapter describes a framework for FRM that can improve urban resilience through participation of local stakeholders with the use of multi-criteria decision analysis (MCDA) tools. First, a systematic review of MCDA studies that tackle flood resilience is presented to provide a better understanding of how participatory MCDA is being conducted. Then, we introduce an innovative FRM participatory approach termed collaborative modelling (CM), which integrates MCDA tools in its process-driven decision-making. Furthermore, the CM-MCDA is supported by user customized Web-based tools to support information dissemination, social learning and negotiation amongst stakeholders. The developed framework was applied in the Cranbrook catchment (London, UK) and in the Alster catchment (Hamburg, Germany). The results show that the CM-MCDA provides an innovative and promising approach to enhance resilience through social learning.
Keywords: Stadtplanung; Hochwasser; Überschwemmung; Hochwasserschutz; Naturkatastrophe; Resilienz; Vorsorge; Risikoanalyse; Risikoabschätzung; Entscheidungsfindung; Modell; Akteur; Interdisziplinarität; Kooperation; Partizipation; Integrierte Planung; Öffentliche Sicherheit; Vulnerabilität; Gefährdung; Kritische Infrastruktur; Bevölkerungsschutz